If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 4m + -4 = 4m Reorder the terms: -4 + 4m = 4m Add '-4m' to each side of the equation. -4 + 4m + -4m = 4m + -4m Combine like terms: 4m + -4m = 0 -4 + 0 = 4m + -4m -4 = 4m + -4m Combine like terms: 4m + -4m = 0 -4 = 0 Solving -4 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.

| 5x+12=5x+13 | | 5=6(q-5)-19 | | 2=11+3(m+3) | | -10+4x-5(x+9)-(x+10)=-15(6-x)-10+4x-5(x-11) | | 5+4(n+9)=-3 | | 0.75(x-2)+.025(x+4)=0.5 | | 0.75(x-2)+0.25(x+4)=0.5 | | 4x+2(4-2(x+2))=2x-4 | | 19x+4-3(x)=-16(14+3-x)-13x+10 | | 4x+16=2x | | -n+15+3n+15=-4 | | 2+5w=9 | | 0.125x=0.025(5x+1) | | 3(6-x)=27 | | 10+2r=8 | | X+3(x+4)=20 | | 18+(2x+9)-(7x-10)=(16-3x)-(10+7-5)-8(9x+4)+11-7 | | -2(6n-5)=-26 | | 22+(-22)= | | 13=1+4s | | 4=9y-4 | | X+6-9x=2-x-5 | | -4-2= | | 2t+7=-1 | | 3(3x-4)=x+3 | | 3-(-8)= | | 17=8x+12 | | X+3=4(4x-6) | | -5(-11x-4)+3(x-5+6)-(10x-5)=7(4x-5+6)+2x-10+(25-10)+4-13 | | x(4x-9)=13 | | 4w-5=16 | | -3+5n=8 | | -x+4x-2(x-8+9)-16+x-5=4x-5+6(4x-5+9)+18-3x | | c+d=e | | 7t+8=-5 | | -3g-8=2 | | x+y=5 | | n-11+5=-4(n+3)-9(8-2n) | | 7x+3y=1 | | 7y+3x=1 | | -8x+2=-3 | | 8x-3=11-6x | | 3x=-9+6 | | 3x=6+-9 | | 15x=10x-30 | | 8x+2x=15x-10 | | 4y+y+1=7(y-1) | | w+3=w+6 | | 8z=4(2z+1) | | 22x+70=17x-95 | | 12y+6=6(2y+1) | | 11a+9=4a+30 | | 8+5x-6=37 | | 3x+12=-10 | | 3(5-x)=2x-x | | x-2.8=1.6 | | 2(x+x+3)=x+2+18 | | 7-5x=2(4+x) | | 5x-7=2(4+x) | | 3(x-5)=2x-x | | 85=21+4n | | 4x-3=4(5-x) | | 3(x+2)-4(3+2x)=0 | | 2(x+x+2)=x+1+18 | | 10x-5y=95 |